2008
DOI: 10.1097/iae.0b013e318074bc1d
|View full text |Cite
|
Sign up to set email alerts
|

Grid Laser Treatment for Exudative Retinal Detachment Secondary to Ischemic Branch Retinal Vein Occlusion

Abstract: Natural history of ERD secondary to ischemic BRVO is poor, and MGLP is able to prevent visual acuity deterioration through a 24-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
1
16
0
2
Order By: Relevance
“…The influence of serous retinal detachment (SRD) on retinal sensitivity in BRVO patients with macular edema remains unclear, even though SRD and cystoid macular edema (CME) often co-exists in these patients when they are examined by OCT,[11-15] although CME is the most common form of macular edema secondary to BRVO. Some authors have reported a poor visual prognosis for BRVO patients with SRD[15-18]. Accordingly, we investigated both visual function (visual acuity and macular sensitivity) and retinal morphology (macular thickness and macular volume) to assess the influence of SRD in BRVO patients with macular edema.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of serous retinal detachment (SRD) on retinal sensitivity in BRVO patients with macular edema remains unclear, even though SRD and cystoid macular edema (CME) often co-exists in these patients when they are examined by OCT,[11-15] although CME is the most common form of macular edema secondary to BRVO. Some authors have reported a poor visual prognosis for BRVO patients with SRD[15-18]. Accordingly, we investigated both visual function (visual acuity and macular sensitivity) and retinal morphology (macular thickness and macular volume) to assess the influence of SRD in BRVO patients with macular edema.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, prognoses vary according to the severity of ischemia, particularly when the ischemia extends to the fovea. 4 In the Zhao et al study, it is difficult to understand how the reported initial visual acuities of patients with foveal subretinal hemorrhage could be higheralthough not statistically so -than those of patients with no subretinal hemorrhage. Nevertheless, final visual acuities were reported as being poorer in their subretinal hemorrhage group of patients.…”
mentioning
confidence: 85%
“…São erros comuns nas análises: (1) inclusão de pacientes com tratamentos prévios, não raro múltiplos; (2)oclusões de ramo analisadas junto com as de veia central numa única amostra; (3) durações prévias diferentes dos quadros; (4) seguimento variável; (5) ausência de controles; (6) falta de randomização e cegamento; (7) amostras pequenas; (8) formas isquêmicas e não isquêmicas determinadas por critérios não uniformes ou discutíveis (como é o caso do CVOS (5) que fez uso das 10 zonas de diâmetro de disco de não perfusão capilar). Assim avolumam-se os relatos sobre anticoagulantes (parnaparina (15) ), trombolíticos (sistêmicos, locais, em doses diferentes (13) , laser "subtreshold" (16) , triancinolona ou antiVEGF intravítreos (8,(17)(18)(19)(20)(21) , complexas cirurgias (22,23) (vitrectomia, neurotomia, canulizações, "sheatotomy" nos cruzamentos vasculares). Hattenbach (13) , mesmo tendo misturado casos com ORV e OVC num mesmo grupo, mostra que a rt-PA foi superior a história natural e aos casos tratados pela iso-hemodiluição quando manejados nos primeiros 10 dias de oclusão.…”
Section: Oclusões Venosas Da Retina -Tendências E Cautelasunclassified
“…Na presença de descolamento sensorial de mácula pode-se obter alguma vantagem, usando uma leve grade (laser limiar) na zona macular (18) . Vem ganhando corpo, aqui e além, a tendência de se testar a validade da pronta instituição de certas terapias (antiVEGF) que possam potencializar a sobrevida dos elementos celulares, combinando-as a alternativas que minimizem os danos tardios (laser focal ou micropulsado) (19)(20) .…”
Section: Oclusões Venosas Da Retina -Tendências E Cautelasunclassified